The compressive strength of lightweight concrete cube with recycled paper as aggregate replacement - Siti Farrah Nadzirah, Awaludin (2015)
Construction field is widely developed from day to day. The development is causing the increasing needs of raw material such as gravel. This high demand is causing the materials becoming extinct. Apart from that, this world also had facing the high amount of waste products which including waste paper. Research has proven that the waste paper can be used as recycled paper in the construction field. The advantages of using the recycled paper is it can help in reducing the amount of waste product as well as preserving the raw material from extinct. However, there is no exact value of compressive strength of concrete containing recycled paper. The type of recycled paper, size and density does affect the compressive strength. Hence, the objective of this research is to determine the compressive strength of papercrete cube with different density of 1.3, 1.4 and 1.5 kg/m3. The other objective of this research is to identify the compressive strength of papercrete cube from three different shredded paper sizes of 2mm x 15mm, 3mm x 25mm and 4mm x 50mm. The total sample of 81 papercrete cubes with a curing period of 7, 14 and 28 days. From the result, the highest 28-day compressive strength is papercrete cube produced by density of 1.5 kg/m3 using shredded paper size of 3x25 mm which is 3.238 MPa. Meanwhile the lowest 28-day compressive strength is papercrete cube produced by density of 1.4 kg/m3using shredded paper size of 4x50 mm which is 1.233 MPa. This shows that the most suitable density is 1.5 kg/m3 with shredded paper size of 3x25mm.